PANTEÃO DA “ORDEM”: intérpretes e estratégias de consagração da “memória franciscana” no Maranhão (1952-2000). - MACHADO, Jorge Luiz Feitoza (2019)
This thesis adresses the construction and consecration logics of memory and identity of Franciscans in Maranhão. From the analysis of a specific laudatory publication, Franciscans in Maranhão and Piauí: 1952-2007, taken as a source and object of analysis, and following the agenda of studies developed at the Laboratory of Studies on Political and Cultural Elites (LEEPOC) we have verified principles of praise and esteem, valued by the official narrative of this congregation, composed by lesser brothers of German origin, which imply recognition and prestige of certain agents. Mainly, we seek to seize the functioning mechanisms of a social domain permeated by hierarchical logics, strategies of collective and individual affirmation and principles of competition. With the support of complementary sources, we discuss the historical and social conditions of the circulation by foreign orders, such as the one we study; social properties and cultural resources favorable on accessing prominent positions on Catholic religious domain, as well as in other fields of activity; and the centrality of associated recognition with the process of singularization of legitimate "causes" such as "education" and "land", whose execution is directly linked to the work of authorized "interpreters".